Tantangan Kerjasama Bilateral Indonesia-Malaysia dalam Perspektif Ekonomi: Perlindungan Pekerja Migran Indonesia di Malaysia dari Perdagangan dan Penyelundupan Manusia - Dwi Valentina Sihite; Alya Rachma; Nabila Amanda Pulungan; Pebriana Asina Panjaitan; Tiffany Laura Balqis; Ulfa Fatimah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research aims to analyze defense cooperation between Indonesia and Germany in weapons procurement. This research involves an analysis of the history of defense cooperation between the two countries, the types of weapons that have been purchased, and the political and military implications of this cooperation. The research method used is the historical study method, namely by reviewing the topic through historical evidence, both written and unwritten, as a reference source. The research results show that defense cooperation between Indonesia and Germany has a significant impact on Indonesia's defense capabilities, but also has political and diplomatic consequences that need to be considered. It is hoped that this research will provide better insight into the dynamics of international defense cooperation and bilateral relations between Indonesia and Germany.